The Correlation Between Students’ Autonomy and Motivation of Third Semester English Department - Sigit Nugroho; Masrur Yahya; Maria Theodora Ping (E3L: Journal of English Language Teaching, Linguistics, and Literature, 2019)
The purpose of this study was to find out the relationship between autonomy and intrinsic motivation of the third semester students of English Department of Mulawarman University academic year 2019/2020. The design of this study was correlational design within quantitative approach. The sample of this study was 73 Third Semester students of English Department of Mulawarman University in academic year 2019/2020. The autonomy questionnaire was adapted from Lin & Reinders (2017) and motivation questionnaire was adapted from Gardner (1985). The data of this study were analyzed using Pearson Product Moment Formula. The data analysis result of autonomy questionnaire showed that third semester English Department students’ autonomy level was 0.392 (M=3.92) and deemed as ‘approaching autonomy’. This result implied that participants had sufficient knowledge and supporting factors to increase their autonomy in learning but not in high rate. The data analysis for the motivation subscale showed that the mean score of students’ motivation was 0.407 (M=4.07), which is considered as high degree of motivation. It can be inferred that the participants had high level of integrative and instrumental motivation. The result of the Pearson Product Formula (0.378) showed that there was a positive and low correlation. Positive correlation means there is a positive relationship between variable as both variables tend to increase or decrease linearly together. This means Null Hypothesis (Ho) is rejected and the Alternative Hypothesis (Ha) is accepted. This result meant that students’ autonomy and motivation can be increased positively in linear manner. However, the correlation is not high since there are many other factors which has relationship with the development of autonomy and motivation